2017
DOI: 10.1515/hmbci-2016-0046
|View full text |Cite
|
Sign up to set email alerts
|

Differential modulation of innate immune response by epinephrine and estradiol

Abstract: Background Although it is widely accepted that catecholamines and estrogens influence immunity and have consequences for health, their effect on innate immunity (e.g. monocytes and neutrophils) is still not fully investigated. Materials and methods Our study aimed to analyze the production of tumor necrosis factor (TNF)-α, interleukin (IL)-1β, monocyte chemoattractant protein (MCP)-1 and IL-8 by whole blood cells following short-term exposure to epinephrine (Epi) and 17β-estradiol (E2) in the presence or absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Additionally, catecholamines can alter cytokine levels and expression of adhesion molecules. Exposure to adrenaline in vitro increases interleukin-8 (IL-8) expression and CD11b (alpha-M-integrin) levels in human neutrophils (4). Under LPS-induced inflammatory conditions the production of IL-1, IL-8, and CCL2 is reduced, indicating that regulation of cytokines and chemokines by adrenaline is highly dependent on the inflammatory milieu (4).…”
Section: Catecholaminesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, catecholamines can alter cytokine levels and expression of adhesion molecules. Exposure to adrenaline in vitro increases interleukin-8 (IL-8) expression and CD11b (alpha-M-integrin) levels in human neutrophils (4). Under LPS-induced inflammatory conditions the production of IL-1, IL-8, and CCL2 is reduced, indicating that regulation of cytokines and chemokines by adrenaline is highly dependent on the inflammatory milieu (4).…”
Section: Catecholaminesmentioning
confidence: 99%
“…in vitro studies showed that after incubation with catecholamines and glucocorticoids, human granulocytes detach more easily by reducing their stiffness (3). In the bloodstream, human neutrophils show increased levels of CD11b as well as IL-8 after stimulation with adrenaline (4). However, their adhesion and trafficking in vitro are reduced due to downregulation of endothelial adhesion molecules (5, 6).…”
Section: Introductionmentioning
confidence: 99%
“…Wahle et al [24] have suggested that β2 adrenoreceptors are the principal factors that mediate cytokine production by PBMC. According to Margaryan et al [13] exposure of non-stimulated whole blood cells to epinephrine showed a dose-dependent increase in IL-8 secretion, whereas LPS stimulated cells expressed a markedly decreased IL-8 and IL-1β production. Howe-…”
Section: Discussionmentioning
confidence: 98%
“…It is evident therefore that increased epinephrine secretion during stress, as in cases of infection and inflammation, will activate the adrenoreceptors on the immune cells and enable them to respond to invading pathogens [12]. Accordingly, exposure of whole blood cells to epinephrine modulated pro-inflammatory cytokine production [13]. In these cases, innate cells, such as specific CD4+CD25− regulatory lymphocytes expressing β2-adrenoceptors, might play a crucial role in inflammation and particularly in sepsis, since when exposed to epinephrine they may restrain the production of pro-inflammatory cytokines [2].…”
Section: Effect Of Epinephrine On Cell Proliferationmentioning
confidence: 99%
“…In fact, epinephrine was found to induce dose-dependently Il-8 production in unstimulated cells, but at the same time it suppressed IL-1β, IL-8, and monocyte chemotactic protein (MCP)-1 secretion in cells stimulated with lPS. 56…”
Section: The Adrenal Gland Microenvironmentmentioning
confidence: 99%